Medical ethics: a brief response to Seedhouse. Issue 1 (February 1995) - Toon, Peter D
Abstract : Medical ethics is that branch of applied philosophy which considers issues of values raised by medical practice, and should not be equated with 'principlism'. Clarification of facts/values distinctions is an important part of this work. The notion that medical philosophy can flourish in the hands of medical 'generalists' without specialist philosophers, is misguided. Both must work together to promote right reason and right action in medical education and practice.